2019
DOI: 10.1002/cjce.23441
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of dynamic asphaltene adsorption on calcite packs: The impact of single and mixed‐salt brine films

Abstract: In this study, the dynamic adsorption of asphaltene on a calcite surface is investigated. This study investigates the effect of mixed-salt brines on asphaltene adsorption. The results of this work can facilitate the understanding of the complex wettability behaviour of carbonate reservoirs. All experiments were performed in porous media, which were sand-packs filled with calcite powder, to study the influence of the type and concentration of salt on adsorption. The experiments were conducted with asphaltene co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 32 publications
(45 reference statements)
5
15
0
Order By: Relevance
“…The pH change is higher for lower initial pH values and lower salinity brines. The pH change in FW and SW is within the error bars as reported already by several researchers. ,,, …”
Section: Resultssupporting
confidence: 89%
“…The pH change is higher for lower initial pH values and lower salinity brines. The pH change in FW and SW is within the error bars as reported already by several researchers. ,,, …”
Section: Resultssupporting
confidence: 89%
“…journal published 16 articles that mention the technique. [43,48,[50][51][52][53][54][55][56][57][58][59][60][61][62][63] The hot topics in the journal relate to the oil industry including asphaltene adsorption on calcite packs, [56] improved heavy oil recovery by injecting alkaline ionic slugs (blue cluster), [54] and rheological properties for composite fluids for fracturing and in mineral processing (green cluster). [58,61] Other topics relate to nanoparticles in polymers (red cluster) and bioimaging, [43,48] drug delivery (red cluster), [50] and environmental remediation (yellow cluster).…”
Section: Applicationsmentioning
confidence: 99%
“…32 Khormali et al 33 experimentally indicated that increasing the initial concentration of asphaltene increased the adsorption onto sandstone and carbonate rocks and the presence of asphaltene inhibitors reduced the amount of asphaltene uptake. 33 Monjezi et al 34 by performing dynamic adsorption tests showed that the presence of a brine film forms a mechanical barrier between the surface of the adsorbent and asphaltenes and leads to a significant decrease in asphaltene uptake. 34 Ahooei et al 11 performed an experimental investigation and modeling of asphaltene deposition on metal surfaces and showed that the structure and composition of asphaltenes highly affected their deposition amount.…”
Section: Introductionmentioning
confidence: 99%
“…33 Monjezi et al 34 by performing dynamic adsorption tests showed that the presence of a brine film forms a mechanical barrier between the surface of the adsorbent and asphaltenes and leads to a significant decrease in asphaltene uptake. 34 Ahooei et al 11 performed an experimental investigation and modeling of asphaltene deposition on metal surfaces and showed that the structure and composition of asphaltenes highly affected their deposition amount. 11 Mohammed et al 18 studied the effect of iron minerals (pyrite, hematite, and magnetite) in increasing wettability alterations of the reservoir rock.…”
Section: Introductionmentioning
confidence: 99%